Clinical usefulness of presepsin and monocyte distribution width (MDW) kinetic for predicting mortality in critically ill patients in intensive care unit - Agnello, Luisa; Ciaccio, Anna Maria; Ben, Fabio Del; Gambino, Caterina Maria; Scazzone, Concetta; Giglia, Aurora; Biundo, Giuseppe; Cortegiani, Andrea; Sasso, Bruna Lo; Ciaccio, Marcello (Frontiers in Medicine, 2024)
Background: In this study, we explored the accuracy of two new sepsis biomarkers, monocyte distribution width (MDW) and Presepsin (PSP), compared to traditional ones, C-reactive protein (CRP) and Procalcitonin (PCT), to identify and monitor sepsis by analysing their kinetic at different time points during hospitalization stay.We enrolled 104 patients admitted to the intensive care unit (ICU) of University Hospital "Paolo Giaccone". Among these, 30 (29%) had a clinical diagnosis of sepsis. MDW, PCT, CRP, and PSP were evaluated at admission (T0), after 24h (T24), 48h (T48), 72h (T72), at day 5 (T5), and at discharge (TD).Results: Patients with sepsis displayed higher levels of PCT and PSP than patients without sepsis at each timepoint; differently, CRP displayed statistically significant differences only at T0, while MDW only at T0 and T24. Patients with increasing levels of PSP displayed lower median survival time than patients with decreasing levels; differences reached statistical significance only at 48h (20 vs 29 days, Log rank test, p=0.046). Interestingly, PSP was an independent predictor of ICU mortality at 48h and 72h after hospital admission. Also, the kinetic of PSP had prognostic value, with increased values at 48h after admission being associated with reduced survival.Our findings support the role of PSP and its kinetic as a predictor of ICU mortality.